El peronismo universitario en un mundo de tensiones Una aproximación a los proyectos de universidad de las organizaciones de estudiantes y docentes peronistas de los setenta - Nicolás Dip (Centre de Recherches sur les Mondes Américains, 2013)
From the analysis of specialized bibliography, documentary and testimonial sources, the present research seeks to generate inputs to contribute to a better understanding of the Peronization process that spanned several university sectors between the university academic units intervention ordered by the civilian-military regime of Juan Carlos Onganía and the appointment of Rodolfo Puiggrós as rector- auditor of porteña house study in the constitutional government of Héctor Cámpora (1966-1973). As part of this problem, the study attempts to reconstruct the political-university itinerary of the main student organizations and teachers who identified with Peronism and university restructuring policies driven from their ranks, with emphasis on the analysis of the National-Popular University project proposed in the magazine Envido. From the objective outlined in the following sections we analyze the positions around the university issue which took the peronist groupings between the mid sixties and early seventies. To deepen the knowledge of them, we investigate the main orientations of the university model proposed in Envido’s pages, through the contrast with the reformist project that contemporaneously raised Risieri Frondizi at The University in a world of tensions.